ANALISIS PENGARUH PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DAN BIG DATA DALAM DUNIA PENDIDIKAN TINGKAT SEKOLAH MENENGAH ATAS DI WILAYAH DKI JAKARTA - Iqsan Felani; Irsyad Ilham Syadra; Esther RB; Agus Nuryadi; Rannisya Firdha Ibrahim (Jurnal Nasional Informatika (JUNIF), 2025)
The development of Artificial Intelligence (AI) and Big Data technology has brought significant changes to the education system, particularly in learning management, evaluation, and data-driven decision-making. This study aims to analyze the impact of AI and Big Data implementation on the quality of learning at the Senior High School level in the DKI Jakarta area. The research method used a quantitative descriptive approach through a survey of 120 teachers and 360 students from 12 public and private high schools. The results show that the implementation of AI and Big Data has a positive impact on learning personalization, the effectiveness of academic evaluation, and the efficiency of school management. This study emphasizes the importance of digital competency development strategies and the provision of supporting facilities to maximize the use of AI and Big Data.